2021
DOI: 10.3389/froh.2021.673449
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Maternal Smoking During Pregnancy and Dental Caries in Children: A Systematic Review and Meta-Analysis

Abstract: Background: Dental caries is a long-standing oral health problem for children all over the world. The available evidence shows that the association between maternal smoking during pregnancy and childhood caries is still controversial. Therefore, the aim of this systematic review and meta-analysis was to determine whether there was a correlation of prenatal smoking and dental caries in children.Methods: PubMed, EMBASE, Cochrane, Web of Science, and Scopus databases were searched for observational studies assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Moreover, Williams, et al (2000) [44] explored parental smoking practices and their connection to caries experience in pre-school children, providing insights into the broader environmental context influencing oral health outcomes in early childhood [44]. A recent systematic review and meta-analysis by Zhong, et al (2021) [45] further corroborated the correlation between maternal smoking during pregnancy and dental caries in children, adding to the growing body of evidence supporting the need for comprehensive preventive measures targeting maternal smoking in the context of oral health promotion [45].…”
Section: Smoking During Pregnancy and Potential Dental Health Implica...mentioning
confidence: 99%
“…Moreover, Williams, et al (2000) [44] explored parental smoking practices and their connection to caries experience in pre-school children, providing insights into the broader environmental context influencing oral health outcomes in early childhood [44]. A recent systematic review and meta-analysis by Zhong, et al (2021) [45] further corroborated the correlation between maternal smoking during pregnancy and dental caries in children, adding to the growing body of evidence supporting the need for comprehensive preventive measures targeting maternal smoking in the context of oral health promotion [45].…”
Section: Smoking During Pregnancy and Potential Dental Health Implica...mentioning
confidence: 99%
“…Mounting evidence evinces fetal and early-life exposure to ETS, even at low levels, increases the susceptibility of dental caries in children and adult life. [6][7][8][9] A recent meta-analysis has demonstrated that children residing with a smoker had significantly higher odds (prenatal-OR: 1.57 (1.47-1.67); postnatal-OR: 1.72 (1.45-2.05)) of presenting with dental caries. 7 ETS, an ubiquitous pollutant, also known as 'passive smoke' or 'secondhand smoke' refers to the mixture of smoke emitted from a burning tobacco product and exhaled by an active smoker.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Emerging evidence indicates that exposure to environmental toxicants such as environmental tobacco smoke (ETS) and metal(loid)s can modify oral health. [6][7][8][9][10]…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 40% of children are exposed to passive smoking globally, with particularly high percentages found in Europe (77.8%) and the Western Pacific (50.6%) 2 . Children exposed to passive smoking show a greater incidence of dental caries, with a significantly higher Decay, Missing, Filled Teeth (DMFT) index compared to control groups not exposed to passive smoking 3 , 4 . The dose-response relationship between the level of passive smoking exposure and DMFT scores provides further supporting evidence.…”
Section: Introductionmentioning
confidence: 99%